Maduramycosis in forearm -A case report - Dr. Jeya Shambavi. J.; Dr. B. Pushpa (Tropical Journal of Pathology and Microbiology, 2018)
Myetoma or Maduramycosis is a chronic granulomatous infection affecting skin and subcutaneous tissue and bone. Mycetoma is caused by Actinomycetes or by fungi such as Madurellamycetomi, Madurellagriesia etc. Eumycetoma is most commonly seen in males. The common site being foot and referred as Madura foot. The organisms present in soil are presumed to be inoculated directly after skin penetration with sharp objects like thorn and gain access to skin and subcutaneous tissue. Multiple nodules develop which suppurate and discharge grains through sinuses during active phase of the disease. We hereby report a case of Twenty year old female presented with painless swelling in right forearm which was clinically diagnosed as Lipoma and biopsy proved it to be Maduramycosis.